Water energy nexus in the people republic of China and emerging issues. - Perera,Pradeep (Metro Manila, Philippines Asian Development Bank, 2017)
Water and energy are both valuable resources and indispensable for human society and economic development. By nature, water and energy are interlinked. Water plays a critical role in the generation of electricity for cooling of thermal power plants and in hydropower, as well as in the production of fossil fuels such as coal; energy is required to treat, distribute, and for wastewater treatment. Choices made in either of the sectors may have unintended and often negative implications on the other sector.
Keywords: Water power -- China; Water rights -- China; Electronic books